2016
DOI: 10.1111/clr.12856
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Schneiderian membrane thickness: a cone‐beam computed tomography analysis with histological validation

Abstract: Within the limitation of this study, the median histological Schneiderian membrane thickness was 0.30 mm. Cone-beam computed tomography assessment was 2.6 times higher than the histological examination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 55 publications
1
20
1
2
Order By: Relevance
“…The mean SMT was 0.64 ± 0.2 mm in our study, which correlates to the findings of Wen et al (2015) and Insua, Monje, Urban, et al (2017)). However, the CBCT assessment was 2.6-fold higher than the histological examination (Insua, Monje, Chan, et al, 2017). In our study, no correlation was found between the membrane thickness and the IoP, which is contrary to the findings reported by Wen and coworkers (Wen et al, 2015) who observed a higher perforation rate in thicker membranes (≥3 mm) or thinner membranes (<0.5 mm).…”
Section: Discussioncontrasting
confidence: 99%
“…The mean SMT was 0.64 ± 0.2 mm in our study, which correlates to the findings of Wen et al (2015) and Insua, Monje, Urban, et al (2017)). However, the CBCT assessment was 2.6-fold higher than the histological examination (Insua, Monje, Chan, et al, 2017). In our study, no correlation was found between the membrane thickness and the IoP, which is contrary to the findings reported by Wen and coworkers (Wen et al, 2015) who observed a higher perforation rate in thicker membranes (≥3 mm) or thinner membranes (<0.5 mm).…”
Section: Discussioncontrasting
confidence: 99%
“…Temmerman et al. reported that both SCA, lateral sinus lift and intra‐lift techniques caused a temporary thickening of the membrane, with a statistically significant change in membrane volume for the lateral sinus lift versus SCA . In this situation, the very limited trauma caused by surgery in our study with a progressive de‐attachment of the membrane may explain that only some membranes suffered with inflammatory thickening and most, even with shrinkage.…”
Section: Discussionmentioning
confidence: 48%
“…Temmerman et al reported that both SCA, lateral sinus lift and intra-lift techniques caused a temporary thickening of the membrane, with a statistically significant change in membrane volume for the lateral sinus lift versus SCA. 17 In this situation, the very limited trauma caused by surgery in our study with a progressive de-attachment of the membrane may explain that only some membranes suffered with inflammatory thickening and most, even with shrinkage. Nonetheless, it should be noted that higher accuracy than 0.5 mm cannot be expected with a clinical use of CBCT 18 and that CBCT measurement might overestimate the histologic real thickness of the membrane 19 ; therefore, measurement of thinner structures like SM might not be totally precise and should be taken cautiously.…”
Section: Discussionmentioning
confidence: 68%
“…38,39 The abutment connection on the endosseous portion of the implant leaves a gap in a range of 10-50 lm. 38 A pumping effect of the fluid contained in the implant cavities might shift inwards to the peri-implant compartment due to the cyclical loading of the implant/abutment interface 38,40 and facilitate the colonization of the gap by putative pathogens. These organic fluids with bacteria products and endotoxins could upregulate the expression of proinflammatory cytokines in the peri-implant tissues and stimulate the chemotaxis of active osteoclasts.…”
Section: Bone Remodeling Processmentioning
confidence: 99%